Influence of hormonal menopausal changes on the clinical course of psoriasis. Psoriasis and menopause: part 2 - Radej, Sebastian; Pietrzak, Aldona; Matosiuk, Dariusz; Wawrzycki, Bartłomiej; Makara-Studzińska, Marta; Figurska, Agata; Gerkowicz, Agnieszka; Kowalczyk, Karolina; Paszkowski, Tomasz; Chodorowska, Grażyna (Menopause Review/Przegląd Menopauzalny, 2012)
Sex hormones are known to influence cutaneous physiology in many different ways. Although hormonal balance is probably best known for its commitment in skin ageing, there is a growing body of evidence that both estrogens and androgens may also have a significant effect on immune response. Modification of the natural course of many chronic inflammatory disorders during pregnancy, menstrual cycle or perimenopausal period suggest a hormonally induced shift in immune balance. In this paper we present and discuss current medical literature about epidemiology and course of psoriasis in the postmenopausal period with respect to hormonal changes.